Cross-disciplinary analysis of the syntactic and lexical features of Chinese master thesis titles - Wang, Zhijie; Abdul Jabar, Mohd Azidan; Mohd Jalis, Farhana Muslim (Academy Publication, 2024)
This study offered a detailed cross-disciplinary analysis of master thesis titles (MTTs) in the fields of Linguistics and Literature, focusing on the variations in title length, syntactic structure, and lexical features. Utilizing a corpus-based approach, the research analyzed 1,000 MTTs from 25 top universities in China, employing both quantitative and qualitative methods to explore how titles reflect disciplinary conventions. The quantitative analysis revealed that Linguistics titles were typically longer and utilized complex nominal structures with a higher lexical density of substantive words, emphasizing precision and detailed content communication. In contrast, Literature titles demonstrated greater syntactic diversity and lexical variety, reflecting a broader thematic scope and adaptability in narrative and thematic expressions. Qualitatively, the study highlighted how these features aligned with the distinct cultural and academic settings of each field. The findings suggested that while Linguistics titles focused on analytical depth, Literature titles incorporated more creative and interpretative elements. This research provided valuable insights into the construction of thesis titles and suggested practical applications for enhancing academic communication across disciplines.